GEOGRAPHICAL POSSIBILITIES OF DEVELOPMENT OF AGROINDUSTRIAL CLUSTER ACTIVITIES IN SAMARKAND REGION - Ibragimov Lutfullo; Boboyev Shodiyor, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article examines the structure and activities of the “Marakand-sifat claster”, created in the Narpai district of the Samarkand region, which presents several activities of the created cluster. In this cluster, a chain dependence is expressed on sowing seeds in the ground before they are processed into a finished product and delivered to the consumer. The huge potential of the Samarkand region in the agriculture of our republic was also assessed, the specifics of the territory, the possibility of growing all types of agricultural products based on statistical indicators were substantiated.